What Factors Drive Purchase Intentions? An Examination of Online Marketplace Users - Lady; Ricky; Isnaini Nuzula (Journal of Enterprise and Development (JED), 2024)
Purpose: The study examines how factors such as perceived usefulness, ease of use, cost, customer trust, satisfaction, and attitude influence online purchase intentions on marketplace platforms.Method: We gathered data through a survey of 310 e-commerce users. The collected data were then analyzed using Partial Least Squares (PLS) with SmartPLS 3.2.9 software to identify and quantify the relationships between the determinants—perceived usefulness, ease of use, cost, customer trust, satisfaction, and attitude—and online purchase intention.Result: The research findings indicate that perceived usefulness, ease of use, cost, customer trust, satisfaction, and attitude all significantly influence online purchase intention. The inclusion of attitude underscores its importance in understanding online shopping behavior.Practical Implications for Economic Growth and Development: This study suggests that enhancing user experience, trust, and satisfaction on marketplace platforms can drive online purchase intentions, ultimately supporting economic growth by boosting e-commerce activity and fostering the development of digital markets.